INDONESIAN LANGUAGE FOR FOREIGN SPEAKERS (BIPA): INDUSTRY-ORIENTED MATERIAL DEVELOPMENT NEEDS ANALYSIS - Yundayani, Audi; Syafri, Frimadhona; Izzati, Arini Noor (LPPM Politeknik Saint Paul Sorong, 2025)
BIPA has gained significant momentum on a global scale since the Indonesian language (IL) became the official language. Due to the high demand for industry-specific material development, researchers conduct a needs analysis regarding IL as a foreign language. From the standpoint of target situation analysis, this study aims to identify the outcomes of a need analysis of foreign learners concerning industrial-oriented IL skills by utilizing a qualitative methodology through a questionnaire. A total of fifty-two people participated voluntarily. The data analysis was qualitative. The findings revealed that IL skills should be related to the industry context, which covers listening, speaking, reading, writing, and knowledge of language structure. It is also essential to reflect metacognitive strategies through the content on material development. These findings will guide the design of learning material and processes by considering the learners' needs and characteristics from the perspective of BIPA as a foreign language.